DOES THE ORIGINALITY REQUIREMENT OF COPYRIGHT STILL HAVE A PURPOSE? - Abdurakhimova Solikha (Modern American Journals, 2025)
Copyright is essential in preserving and promoting creation, but also to maintain public availability of works when applying intellectual property law. Accordingly, protecting copyright is essentially based on "originality" because it demonstrates some degree of inventiveness and is the result of independent innovation. Originality should reflect the author's intellectual effort in the work, rather than the work itself. The requirement of originality as a criterion for copyright eligibility is critical, however it ensures that works based on mechanical effort alone do not receive protection. Such a requirement has caused intense debate: does originality motivate innovation by rewarding new ideas, or it merely places restrictions that interfere with genuine implementations? Drawing on theoretical insights and precedents, intersected with non-legal studies as well as international comparative analysis this essay makes the point that however necessary uniqueness is for innovation incentives in our information society; a simple interpretation of IP Law may impair established cultural or educational practices and therefore indicates procedural reforms.
Keywords: Originality requirement, Copyright law, Intellectual property, Creativity and innovation, Fair use, fair dealing, Digital copyright, Transformative use, Comparative copyright, Creative Commons, Educational access, EU copyright law, U.S. copyright law, Remix culture